2020
DOI: 10.1002/ab.21942
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and peer victimization: A transactional model

Abstract: Past research has shown concurrent associations between adolescent's body mass index (BMI) and classroom bullying victimization experiences. The goal of this three‐wave longitudinal study is to examine a transactional model of associations between BMI and bullying victimization among adolescents in India. We investigate concurrent unidirectional and bidirectional relations between BMI and victimization. In a sample of 1238 students from nine schools (Grades 7–9; M‐ageT1 = 13.15, SD = 1.16) in Indore, India, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…This could be understood as meaning that the relationship between victimisation and higher BMI could be explained by other predictors influencing the model, in this case, cardiorespiratory endurance, while the relationship between BMI and aggression continues to maintain its positive relationship. Therefore, the positive relationships found in normal weight [ 33 ] and obese and overweight [ 32 ] subjects are evident in our study when other predictors of victimisation, such as cardiorespiratory fitness, are not taken into account in the victimisation model. So far, there are studies that have found a relationship between BMI and aggressiveness [ 12 , 45 47 ] although few studies have analysed the role of aggressiveness in bullying.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This could be understood as meaning that the relationship between victimisation and higher BMI could be explained by other predictors influencing the model, in this case, cardiorespiratory endurance, while the relationship between BMI and aggression continues to maintain its positive relationship. Therefore, the positive relationships found in normal weight [ 33 ] and obese and overweight [ 32 ] subjects are evident in our study when other predictors of victimisation, such as cardiorespiratory fitness, are not taken into account in the victimisation model. So far, there are studies that have found a relationship between BMI and aggressiveness [ 12 , 45 47 ] although few studies have analysed the role of aggressiveness in bullying.…”
Section: Discussionmentioning
confidence: 72%
“…Weight and height have been studied in the past associated with bullying. It has been seen a relationship between them although usually the variable body mass index has been used, and relationships have been found with obese and overweight subjects, with normal weight subjects being less studied [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“… Thakkar et al., 2019 India 1238 11–16 School Cohort study NA Psychopathic dimensions taken together serve as a predictor of bullying roles beyond sociodemographic Gender (boys) predicted bullies and bully victims at different times General caste and non Hindu children were more likely to be victims 49. Thakkar et al., 2021 India 1238 11–16 School Cohort study NA No concurrent association between self reported victimization and BMI Concurrent association between BMI and peer reported victimization for boys and girls Higher BMI prospectively predicted lesser victimization for boys 50. Upadhaya et al., 2019 Nepal 35 13–18 School Cross-sectional research NA Bullying is an experience of distress in the community Adolescent bully others who are punished by the teachers or because of their social position Bullying causes emotional harm more than physical harm 51.…”
Section: Resultsmentioning
confidence: 99%
“…It is also bullying when a student is teased a lot in an unpleasant way or when a student is left out of things on purpose. It is not bullying when two students of about the same strength or power argue or fight or when teasing is done in a friendly and fun way.” Global School Based Health Survey— Dema et al., 2019 ; Irish and Murshid, 2020 ; Khan et al., 2020 ; Khan and Khan, 2020 ; Murshid, 2017 , 2018 ; Neupane et al., 2020 ; Pandey et al., 2020 , 2021 ; Rahman et al., 2020 ; Shah et al., 2019 ; Shaikh et al., 2019 ; Wang et al., 2020 NA Instruments used: Adolescent Peer Relation Instrument Mansoor and Shahzad, 2020 Validation study, Bangla translation of the cyber victim part of the cyber victim and bullying scale Mallik and Radwan, 2020 No details given Bullying behaviour scale Abid et al., 2017 No details given Bullying victimization questionnaire SEHER intervention trial— Shinde et al., 2018 , 2020 ; Singla et al., 2021 Coefficient alpha mentioned, translated and contextualized Hindi version of the Korean-Peer Nomination Inventory (K–PNI) Sethi et al., 2019 No details given Illinois Bully scale Sharma et al., 2020 ; Thakkar et al., 2019 , 2021 Coefficient alpha mentioned for English and Hindi versions Illinois Bully scale and Cyber harassment student survey Sharma et al., 2017 No details given International Society for the Prevention of Child Abuse and Neglect Child Abuse Screening Tool for Children Haque et al., 2021 Not details given Interview Naveed et al., 2019 ; Naveed et al., 2020 11 ite...…”
Section: Resultsmentioning
confidence: 99%
“…This could be understood as meaning that the relationship between victimisation and higher BMI could be explained by other predictors influencing the model, in this case, cardiorespiratory endurance, while the relationship between BMI and aggression continues to maintain its positive relationship. Therefore, the positive relationships found in normal weight [33] and obese and overweight [32] subjects are evident in our study when other predictors of victimisation, such as cardiorespiratory fitness, are not taken into account in the victimisation model. So far, there are studies that have found a relationship between BMI and aggressiveness [12,[45][46][47] although few studies have analysed the role of aggressiveness in bullying.…”
Section: Plos Onementioning
confidence: 65%